Fiscal Monitor, April 2019 : Curbing Corruption. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This report discusses fiscal policies to prepare for the next downturn and foster long-term inclusive growth by adapting to changing demographics, advancing technology, and deepening global integration. It also covers recent fiscal developments and the fiscal outlook in advanced economies, emerging markets, and low-income developing countries; recent trends in government debt and analysis of changes in fiscal balances, revenue, and spending; and potential fiscal risks. The report takes on in-depth look at how corruption impacts government policies and operations, the fiscal costs, and how fiscal institutions can help fight corruption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet